2010
DOI: 10.1016/j.eurpsy.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based cognitive therapy for bipolar disorder: A feasibility trial

Abstract: MBCT is feasible and well perceived among bipolar patients. Larger and randomized controlled studies are required to further evaluate its efficacy, in particular regarding depressive and (hypo)manic relapse prevention. The mediating role of mindfulness on clinical outcome needs further examination and efforts should be provided to enhance the persistence of meditation practice with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 20 publications
3
60
1
16
Order By: Relevance
“…There was also no significant treatment by time interaction for depressive or hypo/manic scores over the 12-month period, consistent with the findings of Weber et al (22). This may not be surprising, given that some trials examining psychological interventions such as CBT have also found that the intervention did not reduce relapse to depression or hypo/mania in comparison to a TAU condition (9).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…There was also no significant treatment by time interaction for depressive or hypo/manic scores over the 12-month period, consistent with the findings of Weber et al (22). This may not be surprising, given that some trials examining psychological interventions such as CBT have also found that the intervention did not reduce relapse to depression or hypo/mania in comparison to a TAU condition (9).…”
Section: Discussionsupporting
confidence: 80%
“…However, a later study of MBCT for bipolar disorder (n = 15) reported no significant differences between preand post-treatment mania and depression scores (22). Another study examining the effects at 3-month follow-up noted improvements in depression symptoms, psychological wellbeing, and psychosocial functioning (23).…”
Section: Introductionmentioning
confidence: 99%
“…De nombreux essais contrôlés indépendants ont mis en évidence l'efficacité de la TCBPC dans la prévention de la rechute dépressive, à savoir une diminution des taux de récidivité (de l'ordre de 50 %), des périodes prolongées de rémission inter-épisode, de même que des diminutions des symptômes résiduels qui surviennent immédiatement après le traitement, et même plusieurs années après (Bondolfi et al, 2010 ;Kuyken et al, 2008 ;Kuyken et al, 2010). En outre, on a observé une augmentation dans les mesures liées à la santé du bien-être global et de l'affect positif temporaire (Geschwind, Peeters, Drukker, van Os, et Wichers et al, 2011 ;Godfrin et Heeringen, 2010).…”
Section: Premières Recherches Sur Les Résultatsunclassified
“…Les résultats d'études pilotes ont donné des conclusions encourageantes pour les individus aux prises avec un trouble anxieux social et un trouble anxieux généralisé, y compris une diminution des symptômes d'anxiété et de dépression autoévalués (Evans et al, 2008 ;Piet, Hougaard, Hecksher et Rosenberg, 2010). De plus, deux essais contrôlés provenant de différents centres ont mis en évi-dence des résultats tels que la diminution de l'anxiété et des symptômes dépressifs autodéclarés associés à la participation à la TCBPC chez les individus en phase de rémission pour un trouble bipolaire (Weber et al, 2010 ;Williams et al, 2008). Plusieurs essais contrôlés (Kingston et al, 2007) et ouverts (Finucane et Mercer, 2006 ;Kenny et Williams, 2007 ;Williams et al, 2007) Williams, 2010, p. 10).…”
Section: Tcbpc : Nouvelles Applications Et Innovations Ultérieuresunclassified
“…Thus, these therapies may be suitable for decreasing the chronic, automatic self-criticism that emanates from internalized stigma and impedes functioning (Gilbert et al, 2010). Some studies show that mindfulness-based cognitive therapy (MBCT; Weber et al, 2010;Williams et al, 2008) raised levels of treatment adherence while diminishing stress, anxiety, depression and relapse in BD, all of which improved functioning (Bonvalot et al, 2010;Miklowitz & Johnson, 2009;Richardson, 2010). ACT has been found to diminish internalized stigma in SUD, a common comorbidity of BD (Luoma et al, 2008), warranting research to examine the effects of this intervention on stigma-related thoughts and feelings in BD.…”
Section: Individual Counselingmentioning
confidence: 99%